Consumer preferences for rice attributes in Makassar City (case study of Daya Traditional Market, Terong Traditional Market, and Pabaeng-baeng Traditional Market) - Amran, Farizah Dhaifina (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2025)
The objectives of this study are: 1) Identifying consumer characteristics who purchase rice in Makassar City. 2) Determine the rice quality preferred by consumers. 3) Analyzing the rice attributes that consumers prefer. 4) Assess which attributes are prioritized during rice purchasing decisions. This research was conducted in Makassar City at three different traditional markets: Daya Traditional Market, Terong Traditional Market, and Pabaeng-baeng Traditional Market, with a total of 100 respondents. The data analysis method used is descriptive analysis and conjoint analysis. The results of the study are: 1) The characteristics of respondents are dominated by female respondents with the average age of 42 years, entrepreneur, high school education level, average income of IDR 4,407,470/month, number of family members of 3 people, purchase frequency of 2 times per month, and rice consumption of 16 kg per month. 2) The types of rice quality chosen by respondents are physical characteristics such as size, grain shape, color, and aroma. 3) The rice attributes that consumers prefer are premium rice quality, soft rice, clean, medium shape, pandan-scented rice, shelf life <1 month, price between IDR 12,000–13,000 per kg and rice with a degree of milky whiteness. 4) The rice attribute that consumers consider most in purchasing rice is the quality, with a test value of 22.161. These findings have implications for producers and marketers to enhance the sensory and functional quality of rice, aligning it with consumer expectations. Future research should investigate consumer behavior over time and across different market segments.